Developing a model for an evaluation in elementary mathematics course processes constructivism-based - Ika Victoria Nalurita; Lalu Alwan Junaedi (Math Didactic: Jurnal Pendidikan Matematika, 2019)
In using various models and learning support media there is an evaluation. The purpose of this research to develop an evaluation model of elementary mathematics learning process based on constructivism. The research method used refers to the design model developed by Borg & Gall which the researcher simplifies into 4 stages, namely (1) introduction, (2) development planning, (3) testing, evaluation, revision, and (4) implementation. The subjects of this research were lecturers and the head programs of mathematics education in Gresik with the number of subjects increasing in three trials. Data collection instruments were interview guides, questionnaires and observation sheets. The results of the development of an evaluation model of a elementary mathematics learning process based on constructivism include: evaluation procedures, components, indicators and instruments, as well as evaluation implementation guidelines. Evaluation of the learning process consists of three components, namely: (1) planning evaluation (2) evaluating the implementation of learning and (3) evaluating the implementation of the assessment of learning outcomes. Based on validation and reliability estimation, instruments and guidelines for evaluating the elementary mathematics learning process based on constructivism are included in both categories and the evaluation model of the learning process that has been developed is good and effective based on the assessment of experts, practitioners and users of the model.